Headache in a Child with Pseudohypoparathyroidism: An Alarming Symptom Not to Miss - Sarah Wing-yiu Poon; Brian Hon-yin Chung; Anita Man-ching Tsang; Grace Wing-kit Poon (Case Reports in Endocrinology)
Background. While the endocrine manifestations of pseudohypoparathyroidism are well known, less is known about the associated brain and spine abnormalities. These abnormalities may present with nonspecific symptoms in the paediatric population, and lack of awareness to these uncommon manifestations of the disease may result in a delay in necessary intervention. Case Presentation. We herein present a case of known pseudohypoparathyroidism type 1a who presented initially with minor head injury. She later developed progressive worsening headache, increased irritability, and vomiting. Repeated imaging showed hydrocephalus and Chiari malformation type 1 necessitating emergency craniectomy. Conclusion. Growth hormone deficiency, a common manifestation of pseudohypoparathyroidism type 1a, results in underdevelopment of the posterior cranial fossa and may account for the higher incidence of Chiari malformation in this group of patients. Other associated neurological features reported in pseudohypoparathyroidism type 1a include spinal stenosis, syringomyelia, and craniosynostosis. While less commonly seen, awareness to these associations is important in order to optimize the multidisciplinary care to this group of patients.